Pengaruh Kinesio Taping Terhadap Penurunan Nyeri Musculoskeletal Disorders (MSDs) Pada Kuli PanggulDi Pasar Gede Surakarta - Wulandari, Rahmadini; , Totok Budi Santoso, S.Fis., M.PH (2016)
Background: Musculoskeletal disorders (MSDs) is a disorder of skeletal muscle which are caused by muscle receives a static load continuously for long periods that will cause muscle pain, damage to joints, ligaments, and tendons. One of the jobs that have the risk of musculoskeletal disorders (MSDs) and job burnout is high enough porters. Kinesio taping is a treatment modality that is correct and improve many musculoskeletal disorders which are based on the natural healing process. Objective: Knowing the effects of Kinesio taping on pain reduction of musculoskeletal disorders (MSDs) in the porters at Pasar Gede Surakarta. Metods: This research is a quasi experimental with pre and post test desaign with the control group, ie the sample in the treatment group was given Kinesio taping for 2 weeks with mounting frequency of 2 times a week, with a total sample of 20 porters aged 25-58 years. Pain was measured using a visual analog scale (VAS). Data were analyzed using Wilcoxon test to test the influence and Mann Whitney test to test different influences. Result: There is a positive effect on pain reduction Kinesio taping of musculoskeletal disorders (MSDs) after using a statistical test p-value obtained wicoxon silent pain (ND), tenderness (NT) and the pain of motion (NG) 0,005 in the treatment group. Conclusion: There is a positive effect on pain reduction Kinesio taping of musculoskeletal disorders (MSDs) in the porters at Pasar Gede Surakarta.